The expression of "collectivity" in Romance languages An empirical analysis of nominal aspectuality with focus on French - Kleineberg, Désirée (Beihefte zur Zeitschrift für romanische Philologie, 2022)
The empirical and comparative study examines various facets of the linguistic expression of collectivity in Romance languages. Against the background of an onomasiological conception of nominal aspectuality, collection nouns are analysed with regard to their morphosyntactic and derivational properties, as well as to their diachronic paths of evolution. Special focus is laid on uncountable object mass nouns.